How Are Bankers Paid? - Bennett, Benjamin; Gopalan, Radhakrishnan; Thakor, Anjan (The Review of Corporate Finance Studies, 2021)
Abstract We empirically examine bank CEOs’ compensation. We find that bank CEOs (a) are paid less than their nonfinancial counterparts, an effect driven by the CEOs of small bank; (b) experienced declining compensation during 2007–2009 (the hardest-hit banks cut compensation more) but pay is now 24% higher than precrisis levels; (c) are paid more at larger banks, those with less nonperforming loans, those with a higher proportion of noninterest income, and those with less demand-deposit dependence; and (d) have pay highly sensitive to ROA and ROE, but not stock returns. Tail risk is higher when compensation depends more on short-term measures of performance. (JEL, F34, G32, G33, G38, K42)